Viability of solutions of many-dimensional stochastic differential equations - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish necessary and sufficient conditions for a many-dimensional diffusion process to reside in a fixed domain with probability one.